The application of virtual reality to the simulation of mine fires and explosions - Walsha, Timothy (1999)
Despite significant improvements in mine safety, underground mine fires and explosions are responsible for a significant number of deaths world-wide each year. The training of personnel in safety procedures has had a significant impact on reducing the frequency of injuries and fatalities. This thesis presents an innovative virtual reality simulation, 'Fire-VR', designed to enhance the visualisation of a mine ventilation system. Fire-VR incorporates existing ventilation network analysis procedures with a graphical front-end and offers considerable potential for user interactivity in training scenarios.